2001
DOI: 10.1152/physiolgenomics.2001.6.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic regions controlling plasma FSH concentrations in Meishan-White Composite boars

Abstract: The Chinese Meishan (ME) breed of pig is unique for many reproductive traits. Compared with Western breeds of swine, ME females reach puberty earlier, ovulate more ova per estrus, and have greater uterine capacity, while intact males (boars) have smaller testes and extremely elevated plasma levels of pituitary-derived glycoprotein hormones. In an effort to identify the genetic mechanisms controlling the elevated plasma levels of pituitary-derived glycoprotein hormones [in particular, follicle-stimulating hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…TBG is located within the QTL region for testis size on the X-chromosome (Rohrer et al 2001, McCoard et al 2002a) and is thus a potential candidate factor for regulation of testicular size. While total T 4 levels were greater in MS than WC boars during early postnatal life, circulating levels of free T 4 were not different between breeds, probably resulting from elevated TBG concentrations (decreased T 3 uptake) in MS compared with WC boars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBG is located within the QTL region for testis size on the X-chromosome (Rohrer et al 2001, McCoard et al 2002a) and is thus a potential candidate factor for regulation of testicular size. While total T 4 levels were greater in MS than WC boars during early postnatal life, circulating levels of free T 4 were not different between breeds, probably resulting from elevated TBG concentrations (decreased T 3 uptake) in MS compared with WC boars.…”
Section: Discussionmentioning
confidence: 99%
“…However in boars, plasma folliclestimulating-hormone (FSH) concentrations are not associated with Sertoli cell proliferation during fetal and neonatal life (McCoard et al 2003 -companion paper), the magnitude of the neonatal increase in FSH is not related to adult testicular size (Ford et al 2001), and the increase in FSH secretion following unilateral castration has minimal effect on Sertoli cell proliferation (Lunstra et al 2003). These observations indicate that magnitude of FSH secretion does not play an important role in establishing the number of Sertoli cells in the boar.…”
Section: Introductionmentioning
confidence: 99%
“…A number of pig populations are now being used created for the purposes of searching for litter traits QTLs including crosses between the following breeds: wild boar, Large White, Meishan, Landrace and Duroc. The QTL scan for plasma FSH level in pigs identified several chromosome regions, independent of the FSH, influencing this trait that located on chromosome 3, 8, 10 andX (Linville et al, 2001 andRohrer et al, 2001). A major genetic effect of litter size has been located on SSC 7 (Milan et al, 1998), SSC 8 (Wise et al, 2001) and on SSC 11 (Cassady et al, 2001).…”
Section: Fsh Polymorphisms Discovery and Associationmentioning
confidence: 99%
“…because the additive and dominance effects of the alleles did not differ from zero for any trait. Rohrer et al (2001) identified several trans-acting QTL regulating plasma FSH levels in boars, but no evidence for a cisacting QTL within or near the FSHβ locus was found. In follicles of sows from the Index line, follistatin (FST) was found to be down-regulated (Gladney et al, 2004).…”
Section: Discussionmentioning
confidence: 93%